Legislators and Regional Organizations: The Issue of Legitimacy. (10th May 2019) - Mace, Gordon; Lockhart, Nicolas Falomir
Abstract : Recent scholarship has argued that there has been an opening up of international and regional organizations toward transnational actors since the end of the Cold War, as a result of increased democratization, which is generally considered as a positive contribution to the legitimacy of these organizations. Yet it remains unclear how generalized the opening up has been in terms of regions and category of actors. The role of legislators, particularly outside the European Union, remains understudied even though their presence in regional organizations has increased over the past three decades. This article seeks to fill this void partially by way of a comparative analysis of the role of legislators using the Organization of American States and the Southern Common Market as case studies. The first part of the article offers an overview of the literature and presents our research design. We then proceed with a comparative analysis of the role of legislators at the input, throughput, and output stages of the legitimation process. We conclude with a general assessment of the contribution of legislators as dispensers of legitimacy for regional organizations in the Americas.